2010
DOI: 10.1080/01904167.2010.519089
|View full text |Cite
|
Sign up to set email alerts
|

Dry Bean Genotypes Evaluation for Growth, Yield Components and Phosphorus Use Efficiency

Abstract: 2 Dry bean along with rice is a staple food for the population of South America. In this tropical region beans are grown on Oxisols and phosphorus (P) is one of the most yield limiting factors for dry bean production on these soils. A greenhouse experiment was conducted to evaluate P use efficiency in 20 elite dry bean genotypes grown at deficient (25 mg P kg −1 soil) and sufficient (200 mg P kg −1 ) levels of soil P. Grain yields and yield components were significantly increased with P fertilization and, inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
25
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 28 publications
11
25
0
2
Order By: Relevance
“…As to the present experiment, the existence of genotypic variation in grain yield and yield components (Fageria et al, 2010;Girma et al, 2014;Zewdu, 2014) and the delay in days to maturity (Gidago et al, 2011) with the limited P supply have been reported for common bean. The early flowering with the supply of P observed in present experiment agrees with the report for tomato (Menary and Staden, 1976), wheat (Rahman and Wilson, 1977) and tef (Balcha, 2014).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…As to the present experiment, the existence of genotypic variation in grain yield and yield components (Fageria et al, 2010;Girma et al, 2014;Zewdu, 2014) and the delay in days to maturity (Gidago et al, 2011) with the limited P supply have been reported for common bean. The early flowering with the supply of P observed in present experiment agrees with the report for tomato (Menary and Staden, 1976), wheat (Rahman and Wilson, 1977) and tef (Balcha, 2014).…”
Section: Discussionmentioning
confidence: 91%
“…The differences in genotypes to grow in P limited soils have been reported in several crops such as wheat (Gahoonia et al, 1999;Osborne and Rengel, 2002;Ozturk et al, 2005), maize (Hussein, 2009) and common bean (Fageria et al, 2010) which may be due to differences in changing rhizosphere pH, release of organic compounds, root surface area (Lynch and Brown, 2001;Gahoonia and Nielsen, 2004), production and secretion of phosphatase enzymes by the roots (Yun and Kaeppler, 2001;Wasaki et al, 2003) and use of acquired P in dry matter production (Fohse et al, 1988;Clark and Duncan, 1991). The present experiment was conducted to determine grain yield and yield components and agronomic efficiency of common bean varieties at different P rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large variation in the PS treatment indicates that G. barbadense genotypes are more responsive to P application. Responsive genotypes are more productive and can thus be used as a criterion for selecting and evaluating varieties according to their nutritional efficiency (Fageria et al, 2010).…”
Section: Dry Matter and Phosphorus Contentmentioning
confidence: 99%
“…Phosphorus-efficient genotypes within a species are able to grow well and produce high yields in soils with low available P; they are therefore tolerant to P deficiency (Fageria et al, 2010). Considerable intraspecific variations in P efficiency have been identified in a variety of plant species, including cowpea (Araújo et al, 2012), rice (Fageria and Moraes, 2013), and citrus (Zambrosi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%